Otomasi Sistem Hidroponik Wick Terintegrasi pada Pembibitan Tomat Ceri - Ira Puspasari; Yosefine Triwidyastuti; Harianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Process of maintaining hydroponic wick system manually requires extra energy, especially during the cherry tomato plant breeding season. Parameters, including pH value, Electrical Conductivity (EC) nutrient solution, room temperature, and humidity are needed to be considered to produce superior seeds. In this study, room temperature and humidity, pH value, and EC content in nutrient solution were controlled. The PID and on/off controller were employed in the examination plant. The PID was applied to control room temperature. On the other hand, the on/off was applied to control room humidity, pH, and EC value. PID parameters were set to Kp = 3, Ki = 2, and Kd = 10. As a result, the system produced rise time of 60 minutes, overshoot of 1.17%, and settling time of 57.5 minutes. At the same time, the on/off controller was able to settle the humidity from 61% to 80% within 150 seconds. Moreover, reduction of the pH value from 6.9 to 5.34 can be reached within 12.8 minutes. The study of the EC showed that the longer for the water valve to open, the longer it takes to reach the set point. The study also showed that the rate of cherry tomato plant height is 2.675 cm/week utilizing both of the PID and the on/off controller, while it can only reach 0.2 cm/week without controller. Furthermore, examination on the leaf numbers per week showed that the leaf grew 2 sheets per week when both controllers were applied, while it grew no sheet without controller.